Risk factors for inflammatory bowel disease: an umbrella review - Wu, Tingping; Cheng, Honghui; Zhuang, Jiamei; Liu, Xianhua; Ouyang, Zichen; Qian, Rui (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionInflammatory bowel disease (IBD) represents a cluster of chronic idiopathic inflammatory disorders situated at the nexus of intricate interplays. The primary aim of the present investigation is to perform an umbrella review of metaanalyses, systematically offering a comprehensive overview of the evidence concerning risk factors for IBD.MethodsTo achieve this, we searched reputable databases, including PubMed, Embase, Web of Science, and the Cochrane Database of Systematic Reviews, from inception through April 2023. Two authors independently assessed the methodological quality of each metaanalysis using the AMSTAR tool and adhered to evidence classification criteria.ResultsIn total, we extracted 191 unique risk factors in meta-analyses, including 92 significantly associated risk factors. The top ten risk factors were human cytomegalovirus (HCMV) infection, IBD family history, periodontal disease, poliomyelitis, campylobacter species infection, hidradenitis suppurativa, psoriasis, use of proton pump inhibitors, chronic obstructive pulmonary disease, and western dietary pattern.DiscussionIn conclusion, this umbrella review extracted 62 risk factors and 30 protective factors, most of which were related to underlying diseases, personal lifestyle and environmental factors. The findings in this paper help to develop better prevention and treatment measures to reduce the incidence of IBD, delay its progression, and reduce the burden of IBD-related disease worldwide.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023417175.